2009
DOI: 10.1007/s11252-009-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementing integrated pest management in professional lawn care: a case study

Abstract: Human choices regarding land cover management practices may influence ecosystem services provided by urban green spaces. We conducted a 2-year study to compare biological (weed, insect, and disease), aesthetic (lawn quality), and economic (lawn care program cost) attributes of an integrated pest management (IPM) program, in which pesticides are applied on the basis of treatment thresholds, with a standard program, in which pesticides are applied on a calendar basis without pest monitoring. Both programs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…39 In a comparison of lawn care management programs, 66% of commercial lawn care clients reported dissatisfaction with an intergrated pest management (IPM)-based regimen that allowed ≤5% incidences of weeds and other pest problems, even when the IPM-based program was less expensive than the traditional control program. 40 This observation is consistent with consumer behavior studies in other commodities. For example, Yue et al 41 reported that that consumers' tolerance for cosmetic imperfections 34 Methiozolin dose and application regimen are from the product label (https://www.poacure.com/) and Brosnan et al 33 on apples was quite limited even if the apple is organically produced.…”
Section: A Receptive Marketsupporting
confidence: 86%
See 1 more Smart Citation
“…39 In a comparison of lawn care management programs, 66% of commercial lawn care clients reported dissatisfaction with an intergrated pest management (IPM)-based regimen that allowed ≤5% incidences of weeds and other pest problems, even when the IPM-based program was less expensive than the traditional control program. 40 This observation is consistent with consumer behavior studies in other commodities. For example, Yue et al 41 reported that that consumers' tolerance for cosmetic imperfections 34 Methiozolin dose and application regimen are from the product label (https://www.poacure.com/) and Brosnan et al 33 on apples was quite limited even if the apple is organically produced.…”
Section: A Receptive Marketsupporting
confidence: 86%
“…Over 80% of participants in a Minnesota (USA) sustainable lawn care education program reported that ‘lawn weeds usually require control’ 39 . In a comparison of lawn care management programs, 66% of commercial lawn care clients reported dissatisfaction with an intergrated pest management (IPM)‐based regimen that allowed ≤5% incidences of weeds and other pest problems, even when the IPM‐based program was less expensive than the traditional control program 40 . This observation is consistent with consumer behavior studies in other commodities.…”
Section: A Receptive Marketmentioning
confidence: 99%
“…The reduction of agrochemical inputs has become an increasingly common recommendation in lawn care programmes (Alumai et al, 2010). Morris and Bagby (2008) compared organic and conventional lawn management and found that an organic approach enables savings of $23-29 per year per single-family parcel.…”
Section: Discussionmentioning
confidence: 99%
“…Symbols as in Table 3 Landscape management practices and preferences Homeowner associations often do not directly regulate irrigation, pesticide, or fertilizer use; however, they do require certain yard appearances, which often necessitate the use of these management practices human health (e.g., Karr et al 2007), beneficial urban organisms, or downstream water quality (e.g., Blanchoud et al 2004;Struger and Fletcher 2007). Integrated pest management offers opportunities to reduce these tradeoffs and negative environmental and economic consequences (Braman et al 2000;Klingeman et al 2009;Alumai et al 2010). Watering practices depend on yard cover, irrigation technology and decisions about how much and when to water.…”
Section: Management Decisionsmentioning
confidence: 99%